Massive change - Mau, Bruce (Phaidon, 2004)
Includes transcripts of interviews with: Philip Ball, Janine Benyus, Stewart Brand, Stephen Browne, Carol Burns, James Der Derian, Bill Drayton, Gwynne Dyer, Freeman Dyson, Ian Foster, Felice Frankel, Robert Freling, Ashok Gadgil, Catherine Gray, Hazel Henderson, Dean Kamen, Arthur Kroker, Robert S. Langer, Jaime Lerner, Lawrence Lessig, David Malin, Michael McDonough, William McDonough, Seymour Melman, Nancy Padian, Matt Ridley, Jeffrey Sachs, Richard Smalley, Hernando de Soto, Bruce Sterling and Eugene Thacker.